Identification of genomic regions associated with Ug99 adult plant resistance on wheat (Triticum aestivum L.) - Vikram, Prashant; Lopez-Vera, Eric E.; Bhavani, Sridhar; Thiyagarajan, Karthikeyan; Singh, Sukhwinder (Springer, 2024)
Ug99 is a highly destructive race of stem rust fungus known as Puccinia graminis Pers. f. sp. tritici Eriks. & E. Henn. (Pgt). To address this problem, the International Maize and Wheat Improvement Center, Mexico (CIMMYT) has extensively employed adult plant resistance (APR), which combines multiple genes that provide slow rusting resistance. CIMMYT’s advanced germplasm, “Diniza,” has proven to possess a good level of APR for the Ug99 race group. This study identified the genomic regions responsible for providing APR in the PBW343/Diniza RIL population. Study identified four quantitative trait loci (QTLs) that provide slow rusting APR on chromosomes 2B (QSr.cimm-2B), 3BS (QSr.cimm-3BP1 and QSr.cimm-3BP2), and 7DS (QSr.cimm-7D). These QTLs explained phenotypic variances of 17.0, 18, 8.9, and 11.6%, respectively. Three QTLs, QSr.cimm-2B, QSr.cimm-3BP2, and QSr.cimm-7D, were derived from APR parent ‘Diniza’, while QSr.cimm-3BP1 was derived from ‘PBW343’. Further, QTL class analysis revealed the additive and epistatic interaction results of the identified QTL(s), suggesting that combinations of several QTLs can effectively reduce disease severity. Unlike, QSr.cimm-2B, QTLs QSr.cimm-3BP1 and QSr.cimm-7D co-localized with the previously identified stem rust resistance genes. The identified QTL can be combined to enhance stem rust resistance in breeding materials.